The Charlie Hebdo Attacks on Twitter: A Comparative Analysis of a Political Controversy in English and French. (February 2017) - Smyrnaios, Nikos; Ratinaud, Pierre
In this article, we propose an original method combining large-scale network and lexicometric analysis to link identifiable communities of Twitter users with the main discursive themes they used in the aftermath of the Charlie Hebdo attacks in Paris, France in 2015. We used this method to compare tweets and user networks in French and in English. We observed that the majority of the users who tweeted about Charlie Hebdo were people without any particular affiliation, who were shocked by the attacks and immediately expressed themselves through emotionally charged messages. But rather quickly their proportion decreased and they participated less in politically polarizing discussions. On the other hand, we found that smaller, highly politicized, and polarized groups had similar attitudes toward the events: they were less engaged immediately after the attacks in emotional expression of sympathy and shock, but they participated vividly in the following days in polemical discussions or engaged themes. Other findings include the central position of mainstream media and the existence of groups of users that aggregated on the basis of nationality. More generally, our results show clearly that even the most dramatic events such as a terrorist attack with innocent victims do not produce homogeneous reactions online. Rather, political engagement and cultural dispositions are keys to understand different attitudes on Twitter.